2021
DOI: 10.1101/2021.05.08.443193
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-interval fires and vegetation change in southern California

Abstract: Questions: In southern California, shortened fire return intervals may contribute to a decrease in native chaparral shrub presence and an increase in non-native annual grass presence. To test the hypothesis that short-fire return intervals promote a loss in shrub cover, we examined the contribution of single short-interval fires and abiotic conditions on the change of shrub cover within Ventura and Los Angeles counties. Through evaluating pre- and post-fire historical aerial images, we answered the following q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Although both Meng et al (2014) and Storey et al (2021) have questioned the role of short‐interval fire in explaining VTC in chaparral, and Lucero et al (2021) found weak evidence for it, the results here overwhelmingly point to short‐interval fire and the degree of departure from historical fire return intervals as most important—regardless of the modeling method used or spatial extent of analysis. It is noteworthy that we used here a variable that has not been explored in other work, including our own previous studies—the measure of fire interval departure (vs. minimum fire interval).…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Although both Meng et al (2014) and Storey et al (2021) have questioned the role of short‐interval fire in explaining VTC in chaparral, and Lucero et al (2021) found weak evidence for it, the results here overwhelmingly point to short‐interval fire and the degree of departure from historical fire return intervals as most important—regardless of the modeling method used or spatial extent of analysis. It is noteworthy that we used here a variable that has not been explored in other work, including our own previous studies—the measure of fire interval departure (vs. minimum fire interval).…”
Section: Discussionmentioning
confidence: 55%
“…Another possible reason for the differences in results between our studies and those of Meng et al (2014) and Lucero et al (2021) is that our approach used a historical view of changes over time and theirs relied upon paired plots and a space-for-time substitution. That is, we directly tracked change at one site over time, whereas the other studies inferred change by comparing two sites with different fire histories and then attributed the change to the fire.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations